PandionJ: a pedagogical debugger featuring illustrations of variable tracing and look-ahead - Santos, A. (2017)
We present PandionJ, a pedagogical debugger for Java with innovative features regarding how the program state information is presented to users. We consider aspects that are either not available or not fully automated in existing debuggers (pedagogical or not), such as illustration of the history of variable values and look-ahead of their future state. Our approach relies on static analysis of code in order to infer variable roles, relationships, and behavior. This information is used to render illustrations of program state that existing debuggers are not capable of providing without requiring additional user input.